2012
DOI: 10.1093/aob/mcs158
|View full text |Cite
|
Sign up to set email alerts
|

Floral elaiophore structure in four representatives of the Ornithocephalus clade (Orchidaceae: Oncidiinae)

Abstract: Of the species investigated, most displayed similar anatomical organization, their trichomal elaiophores occurring on the labellar callus. They, thus, differ from many other members of the Oncidiinae, where epithelial elaiophores are found either on the callus, or on the lateral lobes of the labellum. However, ultrastructurally, all elaiophores, whether those of representatives of the Ornithocephalus clade, or those of other oil-secreting Oncidiinae, possessed a similar complement of organelles, regardless of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 16 publications
1
40
0
6
Order By: Relevance
“…This intermediate type of elaiophore is described here for first time in the genus Gomesa; it has previously been described for Ornithocephalus gladiatus Hook. (Pacek et al, 2012), also in Oncidiinae. Pacek and co-workers (Pacek and Stpiczyńska, 2007;Pacek et al, 2012) protection, detoxification, ion balance, tissue support/ plant rigidity, and even the gathering and reflection of light (Franceschi & Nakata, 2005).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This intermediate type of elaiophore is described here for first time in the genus Gomesa; it has previously been described for Ornithocephalus gladiatus Hook. (Pacek et al, 2012), also in Oncidiinae. Pacek and co-workers (Pacek and Stpiczyńska, 2007;Pacek et al, 2012) protection, detoxification, ion balance, tissue support/ plant rigidity, and even the gathering and reflection of light (Franceschi & Nakata, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…(Pacek et al, 2012), also in Oncidiinae. Pacek and co-workers (Pacek and Stpiczyńska, 2007;Pacek et al, 2012) protection, detoxification, ion balance, tissue support/ plant rigidity, and even the gathering and reflection of light (Franceschi & Nakata, 2005). Coté and Gibernau (2012) tested the function of calcium oxalate crystals in floral organs of Araceae relative to pollination strategy and concluded that these crystals protect the plant against insect predation of gametes and embryos and may possibly limit direct feeding by pollinators of some species.…”
Section: Discussionmentioning
confidence: 97%
“…En este trabajo se confirma la presencia de elaióforos florales en Z. alleniana cuyos caracteres estructurales coinciden en líneas generales con los descritos para otras especies del género (Vogel, 1974;Toscano de Brito, 2001;Pacek & Stpiczyn´ska, 2007;Pacek & al., 2012). Los elaióforos de Z. alleniana están formados por tricomas unicelulares, localizados en la base del lóbulo central y en los lóbulos laterales del labelo.…”
Section: Discussionunclassified
“…Dentro del "clado Ornithocephalus" se reportó la presencia de secreción de aceites florales en todos sus géneros (Renner & Schaefer, 2010), aunque solo se describió la estructura del elaióforos en especies de los géneros Ornithocephalus Hook., Phymatidium Lindl. y Zygostates (Vogel, 1974;Toscano de Brito, 2001;Reis & al., 2006;Pacek & Stpiczyn´ska, 2007;Pacek & al., 2012).…”
Section: Introductionunclassified
See 1 more Smart Citation